As repercussões da interiorização da UFPA no trabalho dos docentes da rede estadual de ensino nas décadas de 1980 e 1990 - COSTA, Maria Raimunda Santos da (Universidade Federal do Pará, 2015)
The study aimed to analyze the Brazilian model of expansion of Higher Education after the reforms and public policies addressed to this level of education occurred in Brazil, with attention to the decades of 1980 and 1990, to understand the whole process of installation, materialization and consolidation of moving to the countryside carried out by UFPA (Federal University of Pará), in the so-called “Interiorization Project” in the period studied, in order to identify and unveil the possible effects of that experience in the work of teachers of State schools in the State of Pará. The expansion of Higher Education is the central theme and the repercussions of UFPA’s “Interiorization Project “in the work of public school teachers in Pará are the broad object of this study. The locus of the investigation was the Campus of UFPA located in the City of Santarém, Western Pará, in the Brazilian Amazon. The research sought to know: how was the expansion of public Higher Education in Brazil during the studied period? What were its constraints? What factors contributed for UFPA making real the access to public Higher Education in Pará? What were the effects of UFPA’s “Interiorization Project” in the work of State schools teachers? The study involved bibliographical and empirical research, with an analytical, theoretical and exploratory framework whose methodological assumptions stand bythe dialectic historical materialism. To capture, analyze and unveil the indicators which give materiality to the object of study, we tried to articulate the theoretical knowledge ever produced with the contents of official documents and data collected from fifteen interviewed individuals. The data collection covered the cities of Santarém, Óbidos, Alenquer and Itaituba, which were the early Nuclei bound to the Campus. The study showed that there is a close relationship between changes in the capitalist world and educational reforms and public educational, including job, policies in the country with influence in Brazilian education, its professionals and in the decision of UFPA in moving and consolidate its activities in the hinterlands of Pará, since the very first experience. In virtue of structural constraints, UFPA’s Interiorization Project received many pertinent criticisms, due to the model adopted in the country, which imposed and interposed limitations to the Brazilian Higher Education and its expansion/interiorization process. However, as shown by the statements, it reflected favorably on the work of teachers of State schools in western Pará, in 1980 and 1990, producing effects such as: training in undergraduate level; acquisition of new knowledge; definition of a new professional attitude; wage improvements; possibility, for teachers, to ascend into higher educational levels. Besides that, it represented the initial conditions for the installation and consolidation to offer Higher Education (public and private) in that region. UFPA itself was created in the first formal experience of interiorization that occurred in the country, decreed by President Getúlio Vargas, under the influence of the Francisco Campos Reformation in the 1930s. The expansion of its actions into the countryside was feasible from local, regional, national and international agreements forged in the late 1960s, as part of military dictatorship expansion policies occurred in the country (1964-1985).